Progressing subject-spatial environment project of pre-school organization in Tuva - Sagdy, Chechekmaa; Huren-ool, Stella; Damba, Idegel; Ondar, Chechena; Mongush, Iya (Opción, 2019)
The problems of improving the quality of education and upbringing of the rising generation are becoming topical. This article is dedicated to the improvement of the progressing subject-spatial environment that is a necessary condition for the effective solution of educational challenges when working with children of pre-school age due to establishment of pre-school education Global Environment Facility (GEF). The method of projection activity was applied in the research. The authors are marking the ways of developing the subject-spatial environment with the help of the project activity. This work represents selectively annotated descriptions of the projects.